Role of gut microbiota in bempedoic acid against hyperlipidemia: a new candidate target for bempedoic acid on the therapeutic regulation - Zhang, Wei-Jian; Wang, Jian; Ouyang, Zi-Qi; Luo, Sen-Rong; Chen, Zhi-Kai; He, Yuan-Kang; Luo, Mu-Jin; Liao, Xu-Xing (Frontiers in Pharmacology, 2025)
BackgroundBempedoic acid (BA), an oral synthetic dicarboxylic acid derivative, has been widely used to treat patients with hyperlipidemia who are intolerant to statins. Both clinical and preclinical studies have reported the protective effects of BA against hyperlipidemia. However, the mechanisms of BA for hyperlipidemia treatment remain largely obscured. This study aimed to evaluate the effects of BA on hyperlipidemia and investigate the mechanism underlying its correlation with gut microbiota and serum metabolite regulation.MethodsFour-week-old male C57BL/6J mice were fed a high-fat diet (HFD) and treated with BA daily for 20 weeks. Biochemical changes of serum were assessed, covering lipid metabolism, inflammation, and endothelial function. Moreover, 16S rRNA sequencing of gut microbiota as well as untargeted metabolomics analysis of serum were performed.ResultsThe results showed that BA exerted potent efficacy against hyperlipidemia by attenuating serum lipid profiles, inhibiting vascular inflammation, and improving endothelial function. 16S rRNA sequencing revealed that BA improved the disorder of gut microbiota biodiversity. Specifically, BA significantly enriched the abundance of Akkermansia, Bacteroides, Roseburia, Faecalibacterium and Uncultured_bacterium_f_Muribaculaceae, which were closely associated with BA’s therapeutic effects. Serum metabolomics analysis indicated that BA recovered the disturbances of serum metabolic phenotypes. A total of 20 differential metabolites were significantly regulated by BA treatment, suggesting that BA might exert effects by ameliorating relevant metabolic pathways, including bile acid biosynthesis, glycerophospholipid metabolism, β-oxidation of fatty acids and sphingolipid metabolism.ConclusionTaken together, the present study demonstrated that BA could inhibit the development of hyperlipidemia, and its protective effects may be related to alterations in gut microbiota composition and changes in serum metabolite abundances.